Evaluating the effects of faculty development: theoretical framework and empirical implementation. Issue 2 (2nd April 2020) - Charlier, Bernadette; Lambert, Marie
ABSTRACT: This article implements a systemic framework to evaluate the long-term effects of a program characterized by a SoTL approach and a hybrid learning environment. The importance of the difference between the perception of long-term effects on individual professional development on the one hand and the development of collective practices on the other, is interpreted with reference to certain shortcomings of the faculty development program's learning design and its non-alignment with institutional practices. Based on this in-depth research, concrete ways to take account of the complexity of faculty development programs are proposed, both for research into and development of such programs and their impact at individual and institutional levels.